THE RELATIONSHIP BETWEEN KNOWLEDGE AND SELF-CARE IN ELDERLY PATIENTS WITH HYPERTENSION - Widiasti, Oktawiani Catur; Prakoso, Adi Buyu; Firdaus, Insanul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Hypertension is one of the degenerative diseases commonly experienced by the elderly and is known as the "silent killer." Knowledge of hypertension among the elderly plays an important role in disease control through effective self-care. This study aims to determine the relationship between the level of knowledge and self-care among elderly patients with hypertension in the Working Area of Colomadu II Health Center, Karanganyar Regency. The research method used a quantitative cross-sectional approach with 58 elderly respondents suffering from hypertension who actively participated in the Prolanis program at the Colomadu II community health center. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis employed the Spearman rank test. The results showed that the level of knowledge of the respondents was in the good category (51.7%) and self-care of the respondents was in the good category (79.3%). The results of the Spearman rank test indicated a relationship between the level of knowledge and self-care with a p-value of 0.001 (p-value < 0.005). Good knowledge contributes to optimal self-care behavior.